2012
DOI: 10.1007/s13277-012-0347-x
|View full text |Cite
|
Sign up to set email alerts
|

Human kallikrein-related peptidase 12 (KLK12) splice variants expression in breast cancer and their clinical impact

Abstract: Kallikrein-related peptidases (KLKs) are a group of 15 serine proteases, hormonally regulated, and localized on chromosome 19q13.4. Alternative splicing is a process that plays significant role in the development, physiology, and different diseases, like cancer. Kallikrein family numbers more than 82 alternative transcripts. Understanding the role that those gene transcripts play in various cancer types, could lead to the discovery of diagnostic markers or drug targets. The present study was designed to analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…In contrast, KLK8 and KLK9 expression have been reported to be favorable prognosis in ovarian cancer [19,20]. In addition, KLK12 is reported to be an independent and favorable prognostic marker for breast cancer [21]. Sasaki et al [11] have indicated that there is a significant correlation between decreased KLK11 mRNA expression level and poor prognosis in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, KLK8 and KLK9 expression have been reported to be favorable prognosis in ovarian cancer [19,20]. In addition, KLK12 is reported to be an independent and favorable prognostic marker for breast cancer [21]. Sasaki et al [11] have indicated that there is a significant correlation between decreased KLK11 mRNA expression level and poor prognosis in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Since the probe sequences were quite different, the KLK family may also participate in long-term infection. KLK12 and KLK11 are believed to have diverse functions and may be used as biomarkers for certain kinds of cancers (Lose et al, 2011;Talieri et al, 2012). Downregulated expression of the KLK family may be caused by high levels of tissue factor pathway inhibitor 2 (TFPI2) expression, encoding a serine proteinase inhibitor that may inhibit many serine proteases and plasma kallikrein.…”
Section: Pathway Analysis Of In Vitro Challengementioning
confidence: 99%
“…Note KLK12 mRNA expression is downregulated in breast cancer tissues and is upregulated by steroid hormones in breast and prostate cancer cell lines (Talieri et al, 2012;Yousef et al, 2000). Prognosis KLK12 variant 3 expression is downregulated in breast tumors of small size, high grade, and advanced TNM stage.…”
Section: Breast Cancermentioning
confidence: 98%
“…Prognosis KLK12 variant 3 expression is downregulated in breast tumors of small size, high grade, and advanced TNM stage. Moreover, KLK12 variant 3 overexpression is associated with superior diseasefree survival (DFS) rates for breast cancer patients, as well as with elevated progesterone receptor (PR) concentration (Talieri et al, 2012). (Zhao et al, 2012).…”
Section: Breast Cancermentioning
confidence: 99%